(untitled) (UNED Research Journal, 2016)
Municipal solid waste management is a serious problem in most developing countries and local governments must have reliable information to make decisions. I analized total waste, recoverable waste and organic waste generation in Belén, Heredia, Costa Rica from 2005 through 2015. I found significant differences between the periods 2005-2010 and 2010-2015 (p<.0001), associated with population growth. More waste collection alternatives seem to bring more generated waste (p<.0001). The generation of CH4 in the study period was 52 759.85 Mg of CO2e. The local government should focus on managing organic waste and promote alternative collection methods for recoverable. The evaluation of reliable information and extensive time scales is critical for successful management of solid waste.